Antimicrobial Activities of Some Indonesian Medicinal Plants against Propionibacterium acnes (ATCC 27853) and Staphylococcus epidermis (ATCC 12228) causing Acne - Riris, Ida Duma; Silalahi, Albinus; Juwitaningsih, Tita; Hutabarat, Wesly (Asian Journal of Chemistry, 2019)
Secondary metabolites investigation of local plants, such as Psidium guajava L, Curcuma longa rhizome, Citrus hystrix and Lawsonia intracellularis shown that they have antibacterial activities against Propionibacterium acnes (ATCC 27853) and Staphylococcus epidermis (ATCC 12228) with chloramphenicol as antibiotic controlled. The phytoscreening method used to find out compounds in the plants and inhibition tests carried out by diffuse test with a concentration variation of 10, 5, 2.5 and 1.25 %. It was found that Lawsonia intracellularis plants has the highest inhibitory growth of 17; 12, 15, 14, 12 mm at 10 % concentration.